Assessing additive manufacturing suitability of metal parts: a geometry-focused methodology - Otto Maier; Claudius Ellsel; Dietmar Göhlich (Discover Applied Sciences)
Abstract Additive manufacturing (AM) has the potential to fundamentally change product engineering, enabling the substitution of conventional manufacturing processes. Nevertheless, determining whether transitioning to AM is feasible and advisable is a highly time-consuming and challenging process, influenced by various factors. Existing approaches often require extensive AM expertise or lack the depth needed for reliable conclusions. Therefore, this paper introduces a novel, quantitative methodology that simplifies and supports the decision-making process, primarily based on the part’s geometry. In particular, we evaluate the suitability of metal parts for powder bed fusion laser beam melting (PBF-LB/M) and direct energy deposition-arc metal (DED-Arc/M). The approach assesses three key aspects: manufacturability & adaptation effort, cost estimation, and part complexity. These factors are combined into a comprehensive AM suitability score, supporting informed decision-making. All necessary parameters and thresholds are provided and discussed in detail. Evaluation through expert reviews demonstrates the methodology’s accuracy, practicality, and broad applicability, making it an effective tool for both novice and experienced users.